"A unifying force in the community": Perceptions of a neighborhood park renovation. Issue 3 (27th May 2017) - Pitas, Nicholas A. D.; Hickerson, Benjamin D.; Koerte, Tammy; Kerstetter, Deborah; Mowen, Andrew J.
Abstract: Although the benefits of community parks are well established, evidence supporting the impact of park capital renovations is valuable for organizations seeking funding for such projects. This study assessed stakeholders' perceived impacts as a result of a major park renovation. Separate, semi-structured focus groups were conducted with three stakeholder groups (emerging adults, parents, and older adults). Transcripts were thematically coded using a constant comparison method by multiple team members. Respondents perceived the renovations created a more inclusive and diverse atmosphere, generated social capital, and transformed the park into a "unifying force in the community." Perceived negative impacts included increased usage by certain groups, and crowding in specific locations. This study adds to the body of evidence supporting the impacts of changes to the physical park environment on user behaviors, perceptions, and the social environment within the park and the broader community. Implications for future renovations and interventions are discussed.